The Relationship between Family Support and Elderly Compliance in Visiting Integrated Health Service - Zidane, Muhammad (PHSAJ - Public Health Sebelas April Journal, 2024)
Elderly is someone who has enter 60 years old to above . Elderly is group age in humans who have enter stages from phase end life . The increase age human , will impact on change various things , such as change physical , psychosocial , and spiritual. At the age of dusk , healthy is choice everyone in the world However , at this age late afternoon no everyone can through it with easy , thing it really depends on style life somebody in arrange activities to be able to active and healthy at age dusk (WHO, Daryaman 2021). Research This aiming For analyze connection between support family with compliance elderly in attend Posbindu in RW III Village Sukarapih , District Sukasari , Regency Sumedang in 2024. Research This use design studies observational analytic with cross-sectional approach , involving 55 elderly as respondents . Data collection was carried out through questionnaire that measures level support family and obedience elderly in follow Posbindu.Results chi-square analysis shows existence significant relationship between support family and obedience elderly , with P value of 0.031 (P < 0.05). Of the 42 elderly who received support family well , 22 of them show high compliance to Posbindu , meanwhile only 1 in 4 seniors get support family less have level compliance good . Findings This indicates that support family play a role important in increase compliance elderly in follow a health program like Posbindu.Conclusion from study This is that support family own influence significant to compliance elderly in attend Posbindu . Therefore that , it is necessary existence effort more carry on from family and officers health For increase participation and compliance elderly to existing health programs .